'Fifteen minutes of fame': the 'good Indian', diasporic identities and the American media representation in Thrity Umrigar's If Today be Sweet. (3rd July 2020) - Bhat, Shilpa Daithota
ABSTRACT: Globalized migratory orientations posit tremendous challenges to individual questions of adaptation and acculturation in the host society. This study centers on the discourse of identity formation and the role of media in Umrigar's If Today be Sweet . Positioned relationally and relinquishing lived certainties, Tehmina, the central woman protagonist engages in coping strategies through connecting with people and due to her alertness and sense of protection, happens to attract the attention of the media. While forefronting the argument of migration and cultural integration, it is crucial to consider questions of media's role and international migration and how these shape up individuality. Intense social commitment in the American society helps Tehmina stabilize her identity and position. Her representations in the American media as the 'good Indian' woman evokes questions of how media can define individual identity. In such a context, what do social and cultural differences imply for a migrant woman? Does transnational migration entail circumscribing of individual and social identities? What role do media play in the discursive construction within the text? Through diasporic and media conceptualizations, these questions will be explored through a study of the thematic and cultural particularities in Umrigar's fiction.